Moral issues of paediatric palliative care - Wieczorek, Włodzimierz (Current Problems of Psychiatry, 2011)
The aim of the article is to describe the moral obligations in the context of the pediatric palliative care. The practical aim is to answer the question about proper attitude of the family and the medical staff toward a dying child. The answers take into account the right of the child to the true information about his or her physical state, the possibility of taking part in the decision making process and the spiritual care of the dying children. The theoretical reflections are confronted with the empirical survey among the physicians. The answers for the twelve questions of the questionnaire illustrate the practice of the doctors who deal with the sick children and their families.